Carbon nanotube filler enhances incinerated thermoplastics-induced cytotoxicity and metabolic disruption in vitro - Coyle, Jayme P.; Derk, Raymond C.; Kornberg, Tiffany G.; Singh, Dilpreet; Jensen, Jake; Friend, Sherri; Mercer, Robert; Stueckle, Todd A.; Demokritou, Philip; Rojanasakul, Yon; Rojanasakul, Liying W. (Particle and fibre toxicology, 2020)
Engineered nanomaterials are increasingly being incorporated into synthetic materials as fillers and additives. The potential pathological effects of end-of-lifecycle recycling and disposal of virgin and nano-enabled composites have not been adequately addressed, particularly following incineration. The current investigation aims to characterize the cytotoxicity of incinerated virgin thermoplastics vs. incinerated nano-enabled thermoplastic composites on two in vitro pulmonary models. Ultrafine particles released from thermally decomposed virgin polycarbonate or polyurethane, and their carbon nanotube (CNT)-enabled composites were collected and used for acute in vitro exposure to primary human small airway epithelial cell (pSAEC) and human bronchial epithelial cell (Beas-2B) models. Post-exposure, both cell lines were assessed for cytotoxicity, proliferative capacity, intracellular ROS generation, genotoxicity, and mitochondrial membrane potential. The treated Beas-2B cells demonstrated significant dose-dependent cellular responses, as well as parent matrix-dependent and CNT-dependent sensitivity. Cytotoxicity, enhancement in reactive oxygen species, and dissipation of [DELA]Î¨m caused by incinerated polycarbonate were significantly more potent than polyurethane analogues, and CNT filler enhanced the cellular responses compared to the incinerated parent particles. Such effects observed in Beas-2B were generally higher in magnitude compared to pSAEC at treatments examined, which was likely attributable to differences in respective lung cell types. Whilst the effect of the treatments on the distal respiratory airway epithelia remains limited in interpretation, the current in vitro respiratory bronchial epithelia model demonstrated profound sensitivity to the test particles at depositional doses relevant for occupational cohorts.